Presentation Of Nationalism And Patriotism Values In The 1947 Cadet Film - Baghaswanta, Jeffrey; Hariyanto, Didik (Procedia of Social Sciences and Humanities, 2024)
With the fading of nationalist and patriotic values in society, film is presented as a medium to revive these spirits and values. This study aims to determine the representation of nationalism and patriotism values contained in the 1947 film Kadet by using a qualitative method with John Fiske's semiotic approach. The technique of analyzing the data in this study by analyzing each scene in the 1947 Cadet film that contains the values of nationalism and patriotism was then analyzed using John Fiske's semiotic theory. The results of this study show that the representation of the value of nationalism and patriotism in this film has three stages according to John Fiske including the level of reality, the level of representation and the level of ideology, such as love for the homeland, willingness to sacrifice, bravery, not easily subject to the colonizers, solidarity, and a high spirit of corps.